2016
DOI: 10.1038/srep38873
|View full text |Cite
|
Sign up to set email alerts
|

Roles of human POLD1 and POLD3 in genome stability

Abstract: DNA replication is essential for cellular proliferation. If improperly controlled it can constitute a major source of genome instability, frequently associated with cancer and aging. POLD1 is the catalytic subunit and POLD3 is an accessory subunit of the replicative Pol δ polymerase, which also functions in DNA repair, as well as the translesion synthesis polymerase Pol ζ, whose catalytic subunit is REV3L. In cells depleted of POLD1 or POLD3 we found a differential but general increase in genome instability as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 60 publications
5
38
0
Order By: Relevance
“…Overexpression of RNase H has been shown to significantly reduce both HR and NHEJ efficiency and to delay repair progression via cell-based reporter assays, 17 while immunofluorescence studies have shown that RNase H overexpression impairs repair factor recruitment in response to DNA damage. 68,71,97,98 In addition, co-localisation studies using a fluorescently tagged mutant RNase H that binds to, but does not digest, R-loops has shown rapid relocation to sites of DNA damage, suggesting the formation of R-loops. 17,75 These results indicate that R-loops are generated at break sites to facilitate DDR signal propagation.…”
Section: R-loops: Friend Not Foe?mentioning
confidence: 99%
“…Overexpression of RNase H has been shown to significantly reduce both HR and NHEJ efficiency and to delay repair progression via cell-based reporter assays, 17 while immunofluorescence studies have shown that RNase H overexpression impairs repair factor recruitment in response to DNA damage. 68,71,97,98 In addition, co-localisation studies using a fluorescently tagged mutant RNase H that binds to, but does not digest, R-loops has shown rapid relocation to sites of DNA damage, suggesting the formation of R-loops. 17,75 These results indicate that R-loops are generated at break sites to facilitate DDR signal propagation.…”
Section: R-loops: Friend Not Foe?mentioning
confidence: 99%
“…Interestingly, we have found that at time points > 1h after DNA damage, the association of DNA pol δ p125 subunit was reduced, as compared to early times. In contrast, DNA ligase III and the p66 subunit of DNA pol δ, which is known to interact also with other DNA polymerases (38), were more consistently associated with UDS sites at 4 h after UV damage ( Figure 3C vs Figure 4B). These findings suggest that the pathway employing other DNA polymerases than DNA pol δ, in conjunction with XRCC1 and DNA ligase III, could operate predominantly at sites of heterochromatin, since the typical marker H3K9me3 was associated to UDS sites at late, but not early time points.…”
Section: Discussionmentioning
confidence: 96%
“…While MRN has been implicated in PCNA modification by us and others 46 , the details of this regulation require further study. It is notable that two TLS polymerase subunits, POLD3 and REV3L, have additionally been implicated in preventing R-loop-associated DNA damage 27 . Together, these data suggest that transcription-replication conflicts caused by R-loops are largely handled by the same machinery that deals with chemical DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…This small screen included six known or predicted positive controls (red dots in Fig. 1D) based on studies in yeast (SGS1, TOP1, MPH1 8,14,26 ), or of human orthologues (RAD1/10, POL32) 10,27 . Gratifyingly, all six strains showed significant increases in S9.6 staining providing additional confidence in the assay.…”
Section: Identification Of Rnaseh-dependent Yeast Mutantsmentioning
confidence: 99%